PENERAPAN MODEL PEMBELAJARAN GUIDED DISCOVERY TERHADAP PRESTASI BELAJAR SISWA PADA MATERI GERAK DI KELAS VII SMP NEGERI 1 PUCUK - Heny Ekawati Haryono (JURNAL PENA SAINS, 2017)
Teacher - center method more widely used in the learning process but knowledge gained students less than the maximum. Therefore, The researcher intended to carry out the process of learning that guides the students discover the concept through their own behavior so that the results are more meaningful and is expected to increase the achievement. This research aimed to describe the effect of the application of Guided Discovery model to the students’ achievement, both affective (scientific attitude), psychomotor, and cognitive, as well as to determine the linkages between these aspects. This research was designed using "True Experimental Design" conducted at SMP Negeri 1 Pucuk. The data obtained was the pre-test, post-test, and scores of psychomotor and affective abilities. Furthermore, the data were analyzed with statistical consisting of normality test, homogeneity, and hypothesis testing, and regression and correlation analysis. Post-test results were analyzed by t-test. T-test results obtained by the two parties –ttable t ttable shows the differences between control and experimental class. The t-test results obtained by the right parties  tcalculation≥ ttable (α= 0.05) showed that results for students in the experimental class is better than the control class. It can be concluded that the application of Guided Discovery model can improve the students’ achievement in the material of motion in SMP Negeri 1 Pucuk. The increase in value of the students’ psychomotor and affective effect on the increase in value of the students’ cognitive.